PENGARUH LOKASI KETEBALAN MAKSIMUM AIRFOIL SIMETRIKAL TERHADAP COEFFICIENT DRAG DAN COEFFICIENT LIFT PADA MAIN ROTOR HELIKOPTER BELL 412 - Indra Diantoro; Ardianto Darmanto; Lalu Saefullah (JURNAL MEKANIKASISTA, 2022)
The principle of objects that can move or forces arising from the movement between an object and air is studied in the science of aerodynamics. Great pressure and speed are gaining the science of aerodynamics. In this study, the analysis of aerodynamic characteristics is carried out by testing the object in the form of a model of an aircraft wing or airfoil of similar shape with 3 types of different thicknesses in small scale sizes. The three models were tested using wind tunnel and smoke tunnel to see the resulting air flow and the resulting lift force comparison.In this final project that will be discussed further is the influence of aerodynamics in the world of aviation we are familiar with the coefficient of lift, the coefficient of drag force and also the distribution of the resulting pressure.The method used is simulation analysis method. Simulation is done by making a model of a similar-shaped aircraft wing with a thickness of 15%, 20% and 30%, then tested using a Wind Tunnel and Smoke Tunnel.The purpose of this study was to determine the results of the study variations in the maximum thickness of the symmetrical airfoil using a fixed speed of 20 m/s and an angle of attack of-9o, -6o,-2o 0o, 5o, 10o, 15o against the coefficient of lift, drag coefficient and the maximum pressure distribution.